Principles of toxicology : environmental and industrial applications - Williams, Phillip L. ;James, Robert C. ;Roberts, Stephen M. (Hoboken, New Jersey : John Wiley & Son, Inc., 2000)
This concise volume presents the scientific basis of toxicology as it applies in the workplace and the environment. It covers the diverse chemical hazards encountered in modern work and the natural environment, and provides a practical understanding of these hazards.
1 General Principles of Toxicology 2 Absorption, Distribution, and Elimination of Toxic Agents. 3 Biotransformation: A Balance between Bioactivation and Detoxification 4 Hematotoxicity: Chemically Induced Toxicity of the Blood 5 Hepatotoxicity: Toxic Effects on the Liver. 6 Nephrotoxicity: Toxic Responses of the Kidney 7 Neurotoxicity: Toxic Responses of the Nervous System 8 Dermal and Ocular Toxicology: Toxic Effects of the Skin and Eyes. 9 Pulmonotoxicity: Toxic Effects in the Lung 10 Immunotoxicity: Toxic Effects on the Immune System 11 Reproductive Toxicology 12 Mutagenesis and Genetic Toxicology 13 Chemical Carcinogenesis. 14 Properties and Effects of Metals 15 Properties and Effects of Pesticides 16 Properties and Effects of Organic Solvents 17 Properties and Effects of Natural Toxins and Venoms III APPLICATIONS.
Includes bibliographical references and index.
Keywords: ENVIRONMENTAL TOXICOLOGY